Frequency weightings of hand-transmitted vibration for predicting vibration-induced white finger - Massimo Bovenzi; Iole Pinto; Francesco Picciolo; Marcella Mauro; Federico Ronchese (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVE: The aim of this study was to investigate the performance of four frequency weightings for hand-transmitted vibration to predict the incidence of vibration-induced white finger (VWF). METHODS: In a longitudinal study of vibration-exposed forestry and stone workers (N=206), the incidence of VWF was related to measures of vibration exposure expressed in terms of 8-hour frequency-weighted energy-equivalent root-mean-square (rms) acceleration magnitude [A(8)] and years of follow-up. To calculate A(8), the rms acceleration magnitudes of vibration were weighted by means of four frequency weightings: (i) W_h (the frequency weighting specified in ISO 5349-1:2001); (ii) W_h-bl (the band-limiting component of W_h); (iii) W_hf (a frequency weighting based on finger vibration power absorption); and (iv) W_hT (a frequency weighting based on a Japanese study of VWF prevalence). The relations of VWF to alternative measures of vibration exposure were assessed by the generalized estimating equations (GEE) method to account for the within-subject dependency of the observations over time. RESULTS: Data analysis with a GEE logistic model and a measure of statistical fit suggested that calculating A(8) by weighting the tool rms accelerations with W_h-bl gave better predictions of the cumulative incidence of VWF than the other alternative measures of daily vibration exposure. Values of A(8) derived from the currently recommended ISO frequency weighting Wh produced poorer predictions of the incidence of VWF than those obtained with frequency weightings W_hf or W_hT. CONCLUSIONS: This prospective cohort study suggests that measures of daily vibration exposure which give relatively more weight to intermediate and high frequency vibration are more appropriate for assessing the probability of VWF.